Policy relevant crop diversity monitoring based on earth observation and farmers’ declarations - Marijn van der Velde; Martin Claverie; Raphaël d’Andrimont; Melissande Machefer; Simona Bosco; Rui Catarino; Frank Dentener; Vincenzo Angilieri (Environmental Research Letters)
Comprehensive, wall-to-wall, evaluation of cropping systems and therefore crop diversity using Earth Observation (EO) data is becoming reality. Agricultural policies such as the Common Agricultural Policy (CAP) in the European Union (EU) stimulate more diverse crop-mixes. We compute a new EU-wide overview of crop diversification for 2018 using the Shannon diversity index based on 10 m resolution EO crop map. For the EU as a whole, the effective number of species broadly ranges from 2.6 (p10) to 5.3 (p90) with a median of 3.9. The EO-based map allows identifying how crop diversity varies at an informative spatial resolution, e.g. in areas dominated by mono-cropping or with extensive forest cover. Here we compare the crop diversity calculated from top–down EO-data and bottom–up farmers’ declarations in the Netherlands using the EO-based map (more than 84 millions 10 m pixels) and 2018 Dutch farmers declarations (more than 323 thousands parcels). After accounting for differences in thematic and spatial detail we show agreement in spatial patterns and calculated crop diversification ( R ^2 = 0.62). Furthermore, we track changes in crop diversity over time using the Dutch farmers’ declarations from 2009 to 2021, which suggest a positive response to the 2014 CAP greening policy. Combining the forthcoming Copernicus High Resolution Layers on Crop Types with increasingly available parcel data will enhance spatial targeting of agricultural policies and facilitate the monitoring of policy impact at farm to regional level.